SEGUNDO INFORME DE GOBIERNO 1984 (1984)
CONTENIDO: SECTOR GOBIERNO. -- SECTOR EDUCATIVO. -- SECTORCOMERCIO Y FOMENTO INDUSTRIAL. -- SECTOR SALUD Y SEGURIDADSOCIAL. -- SECTOR TURISMO. -- SECTOR ENERGIA, MINAS E INDUSTRIA PARAESTATAL. -- SECTOR POLITICA EXTERIOR. -- SECTOR AGROPECUARIO Y FORESTAL. -- SECTOR LABORAL. -- SECTOR COMUNICACIONES Y TRANSPORTES. -- SECTOR PESQUERO. -- SECTOR DESARROLLO URBANO Y ECOLOGIA. -- SECTOR POLITICA ECONOMICA. -- INFORME COMPLEMENTARIO